Chatbots in retail: How do they affect the continued use and purchase intentions of Chinese consumers?. Issue 4 (22nd February 2022) - Jiang, Kan; Qin, Meilian; Li, Shurong
Abstract: The application of artificial intelligence in the retail industry has exposed many innovation opportunities and significantly impacts consumer behavior. Based on the social presence, retailer innovativeness, and self‐determination theories, this study constructs an integrated and original framework for elucidating the influence mechanism of the social characteristics of anthropomorphic intelligent services (chatbots) on consumer behavioral intentions. An empirical study of Chinese consumers ( n = 442) reveals the following: first, the social presence of chatbots exerts a direct and positive impact on retailer experience innovativeness and intimacy; second, retailer experiential innovativeness, intimacy, and sense of empowerment mediate the influence of the social presence of chatbots on consumers' behavioral intentions; third, the cute communication styles in the low‐level social presence are very conducive for promoting the relationships between social presence and experiential innovativeness. By improving the level of social presence, formal communication styles can play a key role in promoting relationships. Theoretically, this study contributes to the social presence theory by extending it to the interaction with retailer experiential innovativeness and exploring the chain‐like mediating role of experiential innovativeness, as well as the self‐determined satisfaction between the social presence and consumer behavior intentions. Furthermore, this study also examines how different chatbot communication styles moderate the influence of social presence on consumers' behavioral intentions, thereby revealing the differential effects and boundary conditions of chatbot social presence on consumer behaviors. These findings will offer retailers insights into consumers' psychological activities to practically design chatbots and conduct smart retail innovation activities.